Konflik Laut China Selatan: Rivalitas China-AS dan ASEAN - Herdi Sahrasad (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2015)
Conflict in the South China Sea have significant risk. China, Taiwan, Vietnam, Malaysia, Brunei, and the Philippines have competing territorial and jurisdictional claims, particularly over rights to exploit the region's possibly extensive reserves of oil and gas. Freedom of navigation in the region is also a contentious issue, especially between the United States and China over the right of U.S. military vessels to operate in China's two- hundred-mile exclusive economic zone (EEZ). These tensions are shaping— and being shaped by—rising apprehensions about the growth of China's military power and its regional intentions. China has embarked on a substantial modernization of its maritime paramilitary forces as well as naval capabilities to enforce its sovereignty and jurisdiction claims by force if necessary. At the same time, it is developing capabilities that would put U.S. forces in the region at risk in a conflict, thus potentially denying access to the U.S. Navy in the western Pacific. Given the growing importance of the U.S.-China relationship, and the Asia- Pacific region more generally, to the global economy, the United States has a major interest in preventing any one of the various disputes in the South China Sea from escalating militarily.